Personality-Based Lexical Diferences in Services Adaptation Process - Krzeminska, Izabella; Rzeznik, Jakub (Technium: Romanian Journal of Applied Sciences and Technology, 2021)
In the near future, the reality we live in will undergo a significant transformation caused by the development of advanced information technologies. Artificial intelligence, robots, virtual agents, as well as advanced intelligent virtual services will become ubiquitous. Available digital data and technologies can be used to create new services that are actively adapting to the user. The results presented in the article come from preliminary research indicating how to use data available in digital services to both proling users according to their personality, and providing them with personalised services. We will also present an idea how to use such analyses to create a personalized response from intelligent services. This can have a significant impact on lowering human-machine communication barriers and reducing technological exclusion. It can certainly improve the satisfaction and comfort of using services intelligent enough to be able to self-adapt to a user.